Protection of retinal function by sulforaphane following retinal ischemic injury. (September 2015) - Ambrecht, Lindsay A.; Perlman, Jay I.; McDonnell, James F.; Zhai, Yougang; Qiao, Liang; Bu, Ping
Abstract: Sulforaphane, a precursor of glucosinolate in cruciferous vegetables such as broccoli and cauliflower, has been shown to protect brain ischemic injury. In this study, we examined the effect of systemic administration of sulforaphane on retinal ischemic reperfusion injury. Intraocular pressure was elevated in two groups of C57BL/6 mice (n = 8 per group) for 45 min to induce retinal ischemic reperfusion injury. Following retinal ischemic reperfusion injury, vehicle (1% DMSO saline) or sulforaphane (25 mg/kg/day) was administered intraperitoneally daily for 5 days. Scotopic electroretinography (ERG) was used to quantify retinal function prior to and one-week after retinal ischemic insult. Retinal morphology was examined one week after ischemic insult. Following ischemic reperfusion injury, ERG a- and b-wave amplitudes were significantly reduced in the control mice. Sulforaphane treatment significantly attenuated ischemic-induced loss of retinal function as compared to vehicle treated mice. In vehicle treated mice, ischemic reperfusion injury produced marked thinning of the inner retinal layers, but the thinning of the inner retinal layers appeared significantly less with sulforaphane treatment. Thus, sulforaphane may be beneficial in the treatment of retinal disorders with ischemic reperfusion injury. Highlights: Treatment with sulforaphane after retina ischemia attenuated ischemic-induced loss of retinal function. Treatment with sulforaphane reduced ischemia-mediated thinning of the inner retinal layers. Sulforaphane may have therapeutic value in the management of retinal ischemic disorders.